NEW INNOVATIVE APPROACHES FOR TEACHING A FOREIGN LANGUAGE - Amangul Khulzhanovna Khalzhanova (American Journals, 2022)
The article discusses the inseparability of culture and language, and suggests ways to implement educational strategies for teaching a second language through culture to improve students' linguistic understanding. People living in different regions of the world have different cultural backgrounds and speak different languages. Language and culture are formed at first glance as two separate areas, but they are interconnected and mutually influence each other. The appreciation of a language usually influences the culture associated with it, and cultural patterns of cognition and practices are often explicitly encoded in the language.
Keywords: The article discusses the inseparability of culture and language, and suggests ways to implement educational strategies for teaching a second language through culture to improve students' linguistic understanding. People living in different regions of the world have different cultural backgrounds and speak different languages. Language and culture are formed at first glance as two separate areas, but they are interconnected and mutually influence each other. The appreciation of a language usually influences the culture associated with it, and cultural patterns of cognition and practices are often explicitly encoded in the language.